Climate Change Adaptation Strategies for a Himalayan Hill Town: The Case of Mandi, Himachal Pradesh - Ravjyot Kaur (Calibrating Urban Livability in the Global South, 2024)
The Himalayas are one of the most rapidly urbanizing mountain ecosystems worldwide. Despite being sensitive ecosystems, they have witnessed developments, particularly in the past two decades, that have disregarded this sensitivity when designing and planning for these environments. Climate change, a global phenomenon, is affecting sensitive ecosystems worse. Quite naturally, it also affects the well-being of the inhabitants of these ecosystems. These concerns can be grouped into ecological, morphological, heritage, tourism, and economic. Ecological concerns include construction that disregards the terrain of the natural landscape - development in ecologically sensitive zones, and destruction of the green cover and scenic beauty. These alterations to the natural landscape, in turn, aggravate the impact of disasters. Morphologically, these towns are facing increasing pressure on their indigenous systems, which are also being altered and, in some cases, wholly disregarded to grapple with the newer demands that urbanization and tourism, a significant generator of the economy, are creating. When disasters hit, resilience across genders is also seen differently. Women are often among mountain communities’ vulnerable group to witness climate change’s impact for reasons such as limited access to information, decision-making powers, and adaptive capacity. Climate change has been associated with heavy rainfall, delayed rain and snowfall, flash floods, and even landslides. This paper explores the strengthening of resilience in the case of a climate-induced disaster and urban flooding in the Hill Town of Mandi. It explores human and natural methods that can help strengthen the resilience of these settlements towards climate change particularly in the case of eco-sensitive Himalayan settlements that are grappling with high seismicity risks, landslides, urban flooding, forces of tourism all at once.